Attention Deficits and Rolandic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs)
Impairment in attention in rolandic epilepsy (RE) was evaluated in 14 studies published between 1990 and 2006, in a study at Columbia University Medical Center and Queens College of the City University of New York, NY.